PUBLIC SPACE FUNCTION TRANSFORMATION (CASE STUDY: ENGKU PUTERI SQUARE IN BATAM CITY) - Murtiono, Hendro; Gunawan, I Gusti Ngurah Anom (ASTONJADRO, 2022)
Engku Puteri Square is an open field which is usually called "Alun-Alun”, located next to the mayor's office of Batam which was originally planned as a public open space and venue for the ceremony ground of the Batam City civil servants. The concept of structuring the city square in several cities in Indonesia has been started since a long time ago, the city square has a potential role to be one of the city identities. This is important because we are now experiencing an identity crisis, especially in the field of architecture or urban planning.Engku Puteri square became a different public space when in 2003 the Municipality of Batam decided to construct the fence around the square area, especially when the Alun-Alun was decided to be the location for the implementation of the National MTQ when the Riau Islands Province hosted the event in 2014. A few months before National Level MTQ being held, there were a large renovation done, such as the addition of towers and gates permanently. The pulpit and Astaka used as the main arena of MTQ activities are also built magnificently. The Engku Puteri, which used to have an open concept now becomes more intimate and different from the initial concept, all might be due to the lack of awareness of the public and policy makers about the concept of public open space. The purpose of this paper is to find a concept of the city square that will be compared with the existing conditions as a consideration to restore the actual function of the Engku Puteri City Square.